2002
DOI: 10.5194/angeo-20-1063-2002
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of geomagnetic induction in pipelines

Abstract: Abstract. Geomagnetic field variations induce telluric currents in pipelines, which modify the electrochemical conditions at the pipe/soil interface, possibly contributing to corrosion of the pipeline steel. Modelling of geomagnetic induction in pipelines can be accomplished by combining several techniques. Starting with geomagnetic field data, the geoelectric fields in the absence of the pipeline were calculated using the surface impedance derived from a layeredEarth conductivity model. The influence of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 10 publications
2
62
0
3
Order By: Relevance
“…Similar studies have also been conducted in the Tierra del Fuego region of South America [Osella et al, 1998;Osella and Favetto, 2000]. Large GICs have been correlated with the largest rate of change of the geomagnetic field [Viljanen, 1997;Viljanen et al, 1999;Trichtchenko and Boteler, 2004] and simulations of PSPs on Canadian and Scandinavian pipelines have also been conducted [Boteler and Seager, 1998;Pulkkinen et al, 2001b;Trichtchenko and Boteler, 2002;Fernberg et al, 2007]. GIC signals observed on low-latitude pipelines [Martin, 1993;Waters et al, 2006] are likely to have different ionospheric source fields to those observed on high-latitude pipelines and provide additional spectral information for comparison with model predictions.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…Similar studies have also been conducted in the Tierra del Fuego region of South America [Osella et al, 1998;Osella and Favetto, 2000]. Large GICs have been correlated with the largest rate of change of the geomagnetic field [Viljanen, 1997;Viljanen et al, 1999;Trichtchenko and Boteler, 2004] and simulations of PSPs on Canadian and Scandinavian pipelines have also been conducted [Boteler and Seager, 1998;Pulkkinen et al, 2001b;Trichtchenko and Boteler, 2002;Fernberg et al, 2007]. GIC signals observed on low-latitude pipelines [Martin, 1993;Waters et al, 2006] are likely to have different ionospheric source fields to those observed on high-latitude pipelines and provide additional spectral information for comparison with model predictions.…”
Section: Introductionmentioning
confidence: 76%
“…At high latitudes the Birkeland current system produces large deviations in the geomagnetic field, particularly during disturbed periods. In Finland and Canada, a number of studies have examined GICs and their effects on power transmission lines and oil pipelines [Campbell, 1978[Campbell, , 1986Viljanen andPirjola, 1994a, 1994b;Pulkkinen et al, 2001a;Trichtchenko and Boteler, 2002;Pirjola, 2005;Pulkkinen et al, 2008]. Similar studies have also been conducted in the Tierra del Fuego region of South America [Osella et al, 1998;Osella and Favetto, 2000].…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations